Islamic jurisprudence on harm versus harm scenarios in medical confidentiality - Muhsin, Sayyed Mohamed (Springer Nature, 2024)
Although medical confidentiality is widely recognized as an essential principle in the therapeutic relationship, its systematic and coherent practice has been an ethically challenging duty upon healthcare providers due to various concerns of clinical, moral, religious, social, ethical and legal natures. Medical confidentiality can be breached to protect the patient and/or others if maintaining confidentiality causes serious harm. Healthcare professionals may encounter complicated situations whereby the divulgence of a patient’s confidential information may pose a threat to one party whereas the concealment of such information may cause harm to another. After deliberating on the Islamic concept of harm (ḍarar), this paper focuses on the dual duty and conflicts of interests faced by healthcare professionals in the practice of medical confidentiality. Referring to serious infectious diseases with a special mention of AIDS, this study also provides discourse on how healthcare professionals deal with difficult scenarios of conflicts of interests and ethical dilemmas.